The Hunniwell boys and the platinum mystery - Wyman, L. P. (Levi Parker), 1873-1950; Hastings, Howard L. (Howard Livingston), 1887-1955 (Salt Lake City, UT : Project Gutenberg, 2025)
"The Hunniwell boys and the platinum mystery" by L. P. Wyman is a juvenile aviation adventure novel written in the early 20th century. It centers on brothers Bill and Gordon Hunniwell and Secret Service agent Steve Rogers as they pursue a century-old clue to a hidden cache of precious metal in the Hawaiian Islands. Flying their experimental electric plane, the Albatross, they combine sleuthing with daring flight and face shadowy opposition around Molokai$1 (Bs rugged cliffs. The opening of this novel follows the boys from a Maine fishing trip to a visit by Rogers, who reveals an 1816 attic letter and map hinting at a stash of metal impervious to nitric acid$1 (Blikely platinum$1 (Bhidden on Molokai. They agree to search for it, depart in the Albatross, and make a cross-country-and-Pacific flight marked by a thunderstorm, a ghostly mail-plane encounter, and a close pass over a whale before fog forces a blind landing on a beach. After resupplying in Honolulu, they camp near Laau Point, hear an eerie night wail, and begin searching sea-cliffs between tides. Their battery cells are stolen, but they track down a Japanese thief and recover them; later, someone tries to crush them with a rock from a rift above the shore. Deciding it$1 (Bs unsafe below the cliffs, they reconnoiter from the air and keep guard$1 (Buntil Gordon vanishes from camp. Finding the plane$1 (Bs motor brushes removed, they fit spares, take off, and finally spot a hidden hut in a dense thicket, where the opening section breaks off. (This is an automatically generated summary.)s
Release date is 2025-07-17
Roger Frank and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Brothers -- Juvenile fiction; Aeronautics -- Juvenile fiction; Mystery fiction